Presenting features of polymyalgia rheumatica (PMR) and rheumatoid arthritis with PMR-like onset: a prospective study. Issue 11 (1st November 2001) - Caporali, R; Montecucco, C; Epis, O; Bobbio-Pallavicini, F; Maio, T; Cimmino, M A
Abstract : OBJECTIVE: To evaluate in a prospective study whether patients with polymyalgia rheumatica (PMR) and patients with rheumatoid arthritis (RA) with PMR-like onset show distinctive clinical and laboratory features. METHODS: A cohort of 116 consecutive patients with bilateral girdle pain for at least one month and raised erythrocyte sedimentation rate (ESR) was studied and followed up for 12 months. Laboratory tests included determination of ESR, IgM rheumatoid factor, haemoglobin, white blood cell count, platelet count, percentage of CD8 lymphocytes, serum aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, and glutamyltransferase concentrations. RESULTS: At first examination, RA was diagnosed in 22/116 (19%) patients and PMR in 94 (81%) patients. During the follow up period, 19 additional patients developed RA, and the diagnosis of PMR was confirmed in 65 (56%) patients at the end of the study. Of the clinical and laboratory features, only the presence of peripheral synovitis could differentiate patients who will develop RA from those with "true" PMR, but the positive predictive value of this feature was poor. CONCLUSION: At present, there are no clinical or routine laboratory features allowing early differentiation between PMR and RA with PMR-like onset.